Diagnostics barriers and innovations in rural areas: insights from junior medical doctors on the frontlines of rural care in Peru - Anticona Huaynate, Cynthia Fiorella; Pajuelo Travezaño, Monica Jehnny; Correa, Malena; Mayta Malpartida, Holger; Oberhelman, Richard; Murphy, Laura L; Paz-Soldan, Valerie A (BMC health services research, 2015)
Worldwide, rural communities face barriers when accessing health services. In response, numerous initiatives have focused on fostering technological innovations, new management approaches and health policies. Research suggests that the most successful innovations are those involving stakeholders at all levels. However, there is little evidence exploring the opinions of local health providers that could contribute with further innovation development and research. The aims of this study were to explore the perspectives of medical doctors (MDs) working in rural areas of Peru, regarding the barriers impacting the diagnostic process, and ideas for diagnostic innovations that could assist them. Data gathered through three focus group discussions (FGG) and 18 individual semi-structured interviews (SSI) with MDs who had completed their medical service in rural areas of Peru in the last two years were analyzed using thematic analysis. Three types of barriers emerged. The first barrier was the limited access to point of care (POC) diagnostic tools. Tests were needed for: i) the differential diagnosis of malaria vs. pneumonia, ii) dengue vs. leptospirosis, iii) tuberculosis, iv) vaginal infections and cervical cancer, v) neurocysticercosis, and vi) heavy metal toxicity. Ultrasound was needed for the diagnosis of obstetric and intra-abdominal conditions. There were also health system-related barriers such as limited funding for diagnostic services, shortage of specialists, limited laboratory services and access to telecommunications, and lack of institutional support. Finally, the third type of barriers included patient related-barriers to follow through with diagnostic referrals. Ideas for innovations proposed included POC equipment and tests, and telemedicine. MDs at primary health facilities in rural Peru face diagnostic challenges that are difficult to overcome due to a limited access to diagnostic tools. Referrals to specialized facilities are constrained by deficiencies in the organization of health services and by barriers that impede the patients' travel to distant health facilities. Technological innovations suggested by the participants such as POC diagnostic tools and mobile-health (m-health) applications could help address part of the problem. However, other types of innovation to address social, adaptation and policy issues should not be dismissed.